Clinical Applications of the Microbiome in Obstetrics - Seung Yeon Pyeon; Da Young Kang; So Young Kim; Sun Woo Choi; Moon Yeon Hwang; Young Joo Lee (Korean Society of Neonatology, 2023)
Human microbiome refers to the genetic material of approximately 1013 microorganisms present in the human body. These microbiomes interact significantly with the physiological, metabolic, and immune systems, particularly during pregnancy. Microbiome dysbiosis in pregnant women and their fetuses is associated with obstetric complications and poor neonatal outcomes. Oral and gut microbiomes can influence the placenta, uterus, and fetus via hematogenous translocation. Through ascending translocation, vaginal microbiota can directly affect the uterine environment. Current research focuses on the presence of the placental microbiome, which is characterized by low biomass. However, more well-controlled studies are required to specifically address the contamination issues. Use of antibiotics during pregnancy and the mode of delivery, specifically cesarean section, have been linked to the establishment of the neonatal gut microbiome. Probiotic supplementation may be beneficial during pregnancy, particularly for women receiving antibiotic treatment.